Mechanism of effective depth enhancement and broadband sound absorption optimization in nested resonators with multiple cross-sections - Yiming Zhao; Zichao Guo; Jie Ye; Zhendong Li; Kexin Zeng; Xinying Lu; Zhonggang Wang (Materials & Design)
This study presents a class of three-layer nested sound absorption resonators with multiple cross-sectional features, revealing their sub-wavelength characteristics and broadband sound absorption potential through a series of studies. A precise effective depth calculation method has been proposed to characterize its sound absorption mechanism and the low-frequency shift phenomenon of the sound absorption spectrum caused by the coupling mechanism between discontinuous sections and bent cavities. Experimental verification has demonstrated the feasibility of this method. Parameterization and optimization studies have shown that the outer cavity reduces the actual thickness by approximately 20 % when creating a long-wavelength resonant cavity. The two-dimensional stretched rectangular and equilateral triangular sections exhibit larger effective volumes, resulting in more compact effective sound absorption spectral curves. When the thicknesses of both the optimized 3-layered single unit and the parallel structure are 63 mm, the achieved broadband sound absorption effectively covers the frequency ranges of 365∼790 Hz and 480∼1450 Hz, respectively. This research provides a basic optimization strategy for improving broadband low-frequency sound absorption in nested resonators.